1996
DOI: 10.1606/1044-3894.838
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Permanent Housing for Sheltered Homeless Families

Abstract: The authors analyze 10 years of data on homelessness to determine the characteristics of homeless families most likely to find permanent housing after leaving a shelter environment. They studied 1,156 families from 1983 to 1992 to determine where these families go after leaving the shelter and whether the pattern changed over time. Logistic regression analysis found that the larger the family size and being African American were factors that predicted a decreased likelihood of finding permanent housing. Famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Homeless families were defined as those with a head of household who had a child or children under the age of 18 with them. Researchers have also investigated the characteristics of homeless families (Bassuk and Rosenberg 1988;Goodman 1991aGoodman , 1991bInteragency Council on the Homeless 1996;McChesney 1994;Rog et al 1995;Shinn, Knickman, and Weitzman 1991;Weitzman, Knickman, and Shinn 1992;Wood et al 1990), pathways into homelessness (Bassuk and Rosenberg 1988;Shinn, Knickman, and Weitzman 1991;Weitzman, Knickman, and Shinn 1992), risk and protective factors for family homelessness (Bassuk et al 1997;Shinn et al 1998), and predictors of exit and reentry into family shelters (Rocha et al 1996;Wong, Culhane, and Kuhn 1997). In the subsequent section, we will discuss studies related to the multiply homeless, namely, those that identify factors related to entering and exiting homelessness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Homeless families were defined as those with a head of household who had a child or children under the age of 18 with them. Researchers have also investigated the characteristics of homeless families (Bassuk and Rosenberg 1988;Goodman 1991aGoodman , 1991bInteragency Council on the Homeless 1996;McChesney 1994;Rog et al 1995;Shinn, Knickman, and Weitzman 1991;Weitzman, Knickman, and Shinn 1992;Wood et al 1990), pathways into homelessness (Bassuk and Rosenberg 1988;Shinn, Knickman, and Weitzman 1991;Weitzman, Knickman, and Shinn 1992), risk and protective factors for family homelessness (Bassuk et al 1997;Shinn et al 1998), and predictors of exit and reentry into family shelters (Rocha et al 1996;Wong, Culhane, and Kuhn 1997). In the subsequent section, we will discuss studies related to the multiply homeless, namely, those that identify factors related to entering and exiting homelessness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among different demographic groups, being a homeless family with dependent children was found to have a higher association with the incidence of leaving shelter homelessness, and to have a lower association with the incidence of returning to shelters or the streets (Piliavin et al 1996, Wong, Culhane and Kuhn 1997. A number of studies were further able to identify discharge locations, and thus distinguish if families left homelessness or simply left shelter accommodation (Stretch and Kreuger 1992;Rocha et al 1996). Demographic characteristics such as minority racial status (Rocha et al 1996), the lack of public housing supports (Housing Choice Voucher Program) and sharing lodging with extended families (Stretch and Kreuger 1992) were associated with a lower probability of obtaining permanent housing placement.…”
Section: Causes Of Women's Homelessnessmentioning
confidence: 99%
“…A number of studies were further able to identify discharge locations, and thus distinguish if families left homelessness or simply left shelter accommodation (Stretch and Kreuger 1992;Rocha et al 1996). Demographic characteristics such as minority racial status (Rocha et al 1996), the lack of public housing supports (Housing Choice Voucher Program) and sharing lodging with extended families (Stretch and Kreuger 1992) were associated with a lower probability of obtaining permanent housing placement.…”
Section: Causes Of Women's Homelessnessmentioning
confidence: 99%
“…Two longitudinal studies of former transitional shelter residents in St Louis found that four of ve permanent housing placements were in public housing. Only one in 10 had managed to enter the private housing market (Rocha et al, 1996;Stretch &Krueger, 1992). Results for a six-year New York study found that slightly more than half (56 per cent) of shelter residents made their way to permanent housing.…”
Section: The Challenge Of Social Improvementmentioning
confidence: 99%